Parallel import mechanisms ensure the robust nuclear localization of actin in Drosophila - Borkúti, Péter; Kristó, Ildikó; Szabó, Anikó; Bajusz, Csaba; Kovács, Zoltán; Réthi-Nagy, Zsuzsánna; Lipinszki, Zoltán; Lukácsovich, Tamás; Bogdan, Sven; Vilmos, Péter (Frontiers in Molecular Biosciences, 2022)
Actin, as an ancient and fundamental protein, participates in various cytoplasmic as well as nuclear functions in eukaryotic cells. Based on its manifold tasks in the nucleus, it is a reasonable assumption that the nuclear presence of actin is essential for the cell, and consequently, its nuclear localization is ensured by a robust system. However, today only a single nuclear import and a single nuclear export pathway is known which maintain the dynamic balance between cytoplasmic and nuclear actin pools. In our work, we tested the robustness of the nuclear import of actin, and investigated whether the perturbations of nuclear localization affect the viability of the whole organism. For this aim, we generated a genetic system in Drosophila, in which we rescued the lethal phenotype of the null mutation of the Actin5C gene with transgenes that express different derivatives of actin, including a Nuclear Export Signal (NES)-tagged isoform which ensures forced nuclear export of the protein. We also disrupted the SUMOylation site of actin, suggested earlier to be responsible for nuclear retention, and eliminated the activity of the single nuclear import factor dedicated to actin. We found that, individually, none of the above mentioned manipulations led to a notable reduction in nuclear actin levels and thus, fully rescued lethality. However, the NES tagging of actin, together with the knock out of its importin, significantly reduced the amount of nuclear actin and induced lethality, confirming that the presence of actin in the nucleus is essential, and thereby, over-secured. Supporting this, we identified novel nuclear importins specific to actin, which sheds light on the mechanism behind the robustness of nuclear localization of actin, and supports the idea of essentiality of its nuclear functions.